THE WILD TURKEY STATUS AND OUTLOOK IN 1979 - R. W. Bailey (Wildlife Society Bulletin)
Abstract The wild turkey population in the United States and Canada now numbers about 1,845,000, a nearly 400% increase in the past 2 decades. The harvest rose from 66,400 in 1958 to 222,800 in 1978. The wild turkey occurs in 47 states and 1 Canadian province. It has been reestablished in 15 states and introduced into 11 states and 1 province. Habitat availability is the principal factor that will limit future populations.